Plasmonic coupling architectures for enhanced photocatalysis - Liu, Dong (2022)
Plasmonic photocatalysis is a promising approach for solar energy transformation. Comparing with isolated metal nanoparticles, the plasmonic coupling architectures can provide further strengthened local electromagnetic field and boosted light-harvesting capability through optimal control over the composition, spacing, and orientation of individual nanocomponents. As such, when integrated with semiconductor photocatalysts, the coupled metal nanostructures can dramatically promote exciton generation and separation through plasmonic-coupling-driven charge/energy transfer toward superior photocatalytic efficiencies. Herein, the principles of the plasmonic coupling effect are presented and recent progress on the construction of plasmonic coupling architectures and their integration with semiconductors for enhanced photocatalytic reactions is summarized. In addition, the remaining challenges as to the rational design and utilization of plasmon coupling structures are elaborated, and some prospects to inspire new opportunities on the future development of plasmonic coupling structures for efficient and sustainable light-driven reactions are raised.